THE INFLUENCE OF pH TOWARDS MULTIPLE METAL ION ADSORPTION OF Cu(II), Zn(II), Mn(II), AND Fe(II) ON HUMIC ACID - Buhani Buhani; Suharso Suharso (Universitas Gadjah Mada, 2006)
Multiple metal ions adsorption of Cu(II), Zn(II), Mn(II) and Fe(II) on humic acid with a batch method has been carried out at pH interaction of 3, 5, and 6. Concentration of metal ions in solution before and after interaction was analyzed with Atomic Absorption Spectrophotometer (AAS). Result showed that adsorption multiple metal ions of Cu(II), Zn(II), Mn(II), and Fe(II) on humic acid is optimum at pH 5. Adsorption energies of the multiple metal ions Cu(II), Zn(II), Mn(II), and Fe(II) on humic acid at pH 3, 5, and 6 are around 35.0 - 37.6 kJ/mole. In general, capacity of competition adsorption of the multiple metal ions has an order as follows; Cu(II) < Fe(II) < Zn(II) < Mn(II).